2021
DOI: 10.1016/j.jmig.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Voiding Dysfunction after Surgery for Deep Infiltrating Endometriosis

Abstract: To evaluate the prognostic value of pre-and perioperative factors for voiding dysfunction after surgery for deep infiltrating endometriosis (DIE). Design: Single-center retrospective cohort study. Setting: University hospital. Patients: A total of 198 women with DIE in the posterior compartment who underwent surgery and a postoperative bladder scan. Interventions: Surgical resection of the DIE nodule from the dorsal compartment. Measurements and Main Results: After surgery, 41% of the patients initially experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
0
4
1
1
Order By: Relevance
“…22 Furthermore, this rate has been more recently reported to be as high as 50% by others. 23 The rate of temporary protective ileostomy in our study was 3.64%, which is lower than previous reports. Indeed, in a national snapshot of the surgical management of deep in ltrating endometriosis of the rectum and colon in France in 2015, Roman et al reported a protective stoma rate of 19%.…”
Section: Discussioncontrasting
confidence: 78%
“…22 Furthermore, this rate has been more recently reported to be as high as 50% by others. 23 The rate of temporary protective ileostomy in our study was 3.64%, which is lower than previous reports. Indeed, in a national snapshot of the surgical management of deep in ltrating endometriosis of the rectum and colon in France in 2015, Roman et al reported a protective stoma rate of 19%.…”
Section: Discussioncontrasting
confidence: 78%
“…The risk of surgical complications was lowest in the low-risk group and highest in the high-risk group. Imboden et al ( 2021 ) reported a higher risk of postoperative voiding dysfunction in patients with DE involving the B compartment, especially for B3 lesions. Finally, Nicolaus et al ( 2020 ) found a statistically significant 3.5-fold increased risk of Clavien-Dindo complications grade II or higher in the presence DE in the Enzian score.…”
Section: The Enzian and (#) Enzian Classificationsmentioning
confidence: 99%
“…In a comprehensive literature review, Campin et al reported varying risk of post-operative voiding dysfunction ranging from 0.8 to 30% 21 . Furthermore, this rate has been more recently reported to be as high as 50% by others 22 .…”
Section: Discussionmentioning
confidence: 81%